Making sense of significance in environmental impact assessment. Issue 1 (2nd January 2016) - Jones, Megan; Morrison-Saunders, Angus
Abstract: Impact significance determination lies at the heart of environmental impact assessment (EIA) but conflict and misunderstanding around the concept is common. This paper attempts to make sense of impact significance in EIA based on four essential components of significance synthesised from the literature to ensure that: (1) a clear operational framework for significance determination applies throughout EIA, (2) attention focuses only on significant issues, (3) the term significance is specified and applied consistently, and (4) significance determinations are transparent to all EIA stakeholders. To provide a practical perspective, the extent to which EIA institutional provisions in Western Australia uphold these significance determination components is reviewed. Overall the Western Australian approach generally meets all four components, but areas for improvement include better guidance encouraging proponents to adopt a more consultative approach to determining relevant environmental factors and objectives to better focus EIA, and distinguishing between terms used for significance within EIA documentation. A new significance framework approach in Western Australia represents a clear attempt to uplift practice, but opportunity exists to improve the way impact significance determinations are presented to stakeholders. EIA practitioners may benefit from mapping and making sense of impact significance in their own jurisdiction using the four components presented.